2017
DOI: 10.1002/jat.3507
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the internalization and toxicological profile of silica nanoparticles and submicroparticles for the design of dermal drug delivery strategies

Abstract: The use of colloidal silica nanoparticles and sub-microparticles (SiPs) have been considered a very interesting strategy for drug delivery applications. In the present study, we have focused our attention on the suitability of these nanomaterials as potential carriers for dermal drug delivery, thus studying their toxicological profile in vitro, cellular uptake and intracellular localization in both human keratinocytes (K17) and human dermal fibroblasts (HDF) as a function of their particle size (SiPs of 20, 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Section 3.2 ), and hence the manner in which they come into contact with the cultured cells [ 80 ]. However, the cellular uptake of colloidal SiO 2 nanoparticles also appears to depend on the type of cultured cells [ 81 ], and noninternalized particles can also damage the cell membrane, and hence induce cellular effects, by diffusion contact [ 74 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Section 3.2 ), and hence the manner in which they come into contact with the cultured cells [ 80 ]. However, the cellular uptake of colloidal SiO 2 nanoparticles also appears to depend on the type of cultured cells [ 81 ], and noninternalized particles can also damage the cell membrane, and hence induce cellular effects, by diffusion contact [ 74 , 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tokgun et al 23 demonstrated that among 6, 15, and 30 nm sizes of aSiNPs, 6 nm-sized nanoparticles had strongest cytotoxic effects on A549 cells, and this cytotoxicity came from dead receptor-mediated induction of apoptosis. Liu et al 24 examined the cell viability of A549 cells after exposing to SiO 2 particles at various concentrations (5,10,20,30,40,60,80, and 100 μg/mL). Results of CCK-8 assay showed that exposures of 10-20 nm aSiNPs resulted in significantly decreased viability of A549 cells, while 5 μm SiO 2 particles did not affect the cell viability obviously.…”
Section: Size-dependent Cytotoxicity Of Asinps Size-dependent Cytotoxmentioning
confidence: 99%
“…Li et al 28,29 investigated the possible cytotoxicity of three sizes of aSiNPs (40,60, and 200 nm) in human bronchial epithelial BEAS-2B cells. These particles inhibited the cell viability in a size-dependent manner, the smaller aSiNPs produced higher toxic effect.…”
Section: Size-dependent Cytotoxicity Of Asinps Size-dependent Cytotoxmentioning
confidence: 99%
See 2 more Smart Citations